PENGARUH PENERAPAN VIDEO ANIMASI PADA MATERI MEMELIHARA KESEHATAN ORGAN PERNAPASAN MANUSIA TERHADAP HASIL BELAJAR SISWA KELAS IV DI MI ASSALAM BANGKINANG - Ramadhanis Sitompul, Iren; Alexander Alim, Jesi; Hainul Putra, Zetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of animated videos as a medium to facilitate the delivery of learning material on students' learning outcomes. The data for this research was obtained through a quantitative pre-experimental method with a one-group pre-test and post-test design. The subjects of this study consist of 31 students in the fourth grade of MI Assalam Bangkinang. To determine the research results, the testing technique used involves pre-test and post-test questions. The analysis using the Paired Sample T-Test with IBM SPSS Statistic 27 aims to determine the effect of animated video media on students' learning outcomes. The analysis using the Paired Sample T-Test indicates a significant effect on students' learning outcomes after the implementation of animated video media in science lessons in the fourth grade at MI Assalam Bangkinang. The Sig. (2-tailed) value of 0,000 indicates less than 0.05, leading to the conclusion that Ho is rejected and Ha is accepted.